2014
DOI: 10.11114/jets.v2i2.252
|View full text |Cite
|
Sign up to set email alerts
|

Materialism, Stress and Health Behaviors among Future Educators

Abstract: In this study we investigated materialism among future educators and its relationship with stress and a number of health behaviors. Participants were 228 students (Mean= 20.64 years of age, S.D= 2.571) of the Department of Education Sciences in Early Childhood of the University of Thrace, Greece.The instrument consisted of a short form of the Material Values Scale with three subscales, pertaining to the following three domains: possession-defined success, acquisition centrality and acquisition as the pursuit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
2
17
2
4
Order By: Relevance
“…Material pursuits help to meet the need for uniqueness and belonging, and can compensate for threatened self-esteem, because people believe that material and wealth make them more socially attractive, or react to the threat of self-esteem, especially when people think when they are excluded by society (Jiang et al, 2015). In addition, material wealth can help restore and maintain a sense of stability, identity, control and positive self-image, and is a means of reducing stress (Brouskeli & Loumakou, 2014).…”
Section: The Influence Of Materialism On the Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Material pursuits help to meet the need for uniqueness and belonging, and can compensate for threatened self-esteem, because people believe that material and wealth make them more socially attractive, or react to the threat of self-esteem, especially when people think when they are excluded by society (Jiang et al, 2015). In addition, material wealth can help restore and maintain a sense of stability, identity, control and positive self-image, and is a means of reducing stress (Brouskeli & Loumakou, 2014).…”
Section: The Influence Of Materialism On the Individual Levelmentioning
confidence: 99%
“…Because of the importance of external goals, high-level materialists have unmet internal needs and have many negative effects on individuals' psychology, emotions, and behaviors. For example, materialism and well-being Wang et al, 2017b), self-realization (Kasser & Ahuvia, 2002), life satisfaction Psychology Shrum et al, 2013 Meet the need for uniqueness and belonging Wong et al, 2011 Make up for threatened self-esteem Wong et al, 2011Jiang et al, 2015 Relieve pressure Brouskeli & Loumakou, 2014 Reduce happiness Kasser et al, 2014Wang et al, 2017b Reduce life satisfaction Tsang et al, 2014 Reduce the quality of life Roberts & Clement, 2007 Less positive emotions, higher levels of depression, loneliness, anxiety and substance abuse Kasser & Ryan, 1993, 1996Pieters, 2013 Reduce self-awareness, quality of relationships, and willingness to participate in community activities Kasser & Ahuvia, 2002 Consumption level promoting economic prosperity and social progress Sirgy et al, 2013 Driving fashion innovation Goldsmith et al, 2013 Marketing staff design promotional information Heath & Chatzidakis, 2012 Poor money management skills Donnelly et al, 2013 More gambling problems Carver & McCarty, 2013 Accumulate huge debts Watson, 2003 Compulsive consumption Donnelly et al, 2013Dittmar et al, 2014 Conspicuous consumption Podoshen, Li, & Zhang, 2011 Positively related to consumer behavior and attitudes triggered by hedonism, image and status values Dittmar et al, 2014Kamal et al, 2013Workman & Lee, 2011Srivastava et al, 2001 Organizational level Work hard to complete challenging tasks Vohs, Mead, & Goode, 2006 Increase the profits of enterprises and create funds for research and development Richins & Rudmin, 1994Kasser et al, 2007 Lower quality of work life…”
Section: The Influence Of Materialism On the Individual Levelmentioning
confidence: 99%
“…Materialisme yang tinggi adalah sebab bagi berbagai persoalan psikologi, sosial, ekonomi, dan pendidikan, seperti: rendahnya well-being, ketidakbahagiaan dan ketidakpuasan hidup, dan tingginya stres dan depresi (Brouskeli & Loumakou, 2014;Dittmar & Kapur, 2011;Garðarsdóttir, Janković & Dittmar, 2008;Karabati & Cemalcilar, 2010;Konow & Earley, 2008;Tatzel, 2002;Tsang, Carpenter, Roberts, Frisch, & Carlisle, 2014); perilaku mengkonsumsi yang bermasalah, seperti compulsive dan excessive buying (Dittmar, 2005;Müller, et al, in press, 2011;Pham, Yap, & Dowling, 2011); sikap dan perilaku tidak prolingkungan (Hurst, Dittmar, Bond, & Kasser, 2013;Kilbourne & Picket, 2008); sikap negatif terhadap pernikahan dan memiliki anak (Li, Patel, Balliet, Tov, Scollon 2010); ketidaksukaan menabung dan sekolah pada anak, rendahnya motivasi belajar intrinsik, meningkatnya motivasi belajar ekstrinsik, dan rendahnya performa akademik (Goldberg Gorn, Peracchio, & Bamosy, 2003;Ku, Dittmar, & Banerjee, 2014).…”
Section: Studi Materialisme Awal: Konsekuensi Dan Antesedenunclassified
“…They therefore see materialism as an identity builder. Brouskeli and Loumakou (2014) found that materialism is a stress buffer. While these researchers see materialism as playing a positive role, most researchers however view materialism as an inescapable and an undesirable aspect of consumer culture , which leads to a number of negative consequences.…”
Section: Introductionmentioning
confidence: 99%